2020
DOI: 10.3390/ani10061004
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Enteric Methane Emission Measurement Techniques in Ruminants

Abstract: To identify relationships between animal, dietary and management factors and the resulting methane (CH4) emissions, and to identify potential mitigation strategies for CH4 production, it is vital to develop reliable and accurate CH4 measurement techniques. This review outlines various methods for measuring enteric CH4 emissions from ruminants such as respiration chambers (RC), sulphur hexafluoride (SF6) tracer, GreenFeed, sniffer method, ventilated hood, facemask, laser CH4 detector and portable accumulation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 86 publications
(169 reference statements)
0
36
0
Order By: Relevance
“…Wind direction has been suggested as one of the major factors potentially affecting methane measurements in grazing studies [ 4 , 32 ]. However, as we have found that wind speed during our measurements did not influence the modified SF 6 technique, and as cows orient themselves in many directions at different times during the day, we also surmise that wind direction does not influence the technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind direction has been suggested as one of the major factors potentially affecting methane measurements in grazing studies [ 4 , 32 ]. However, as we have found that wind speed during our measurements did not influence the modified SF 6 technique, and as cows orient themselves in many directions at different times during the day, we also surmise that wind direction does not influence the technique.…”
Section: Discussionmentioning
confidence: 99%
“…The respiration chamber method is considered the “gold standard” [ 1 ] and has been used by many researchers over the past 5 decades. Two recently developed methods include the sniffer method [ 2 ] and the Greenfeed or C-lock method [ 3 ] which have been increasingly used in recent research [ 4 ]. However, due to the limited sampling times used in these latter methods [ 5 ], and the marked diurnal patterns in the magnitude of MeP from dairy cows [ 6 ], some researchers have questioned the suitability of these recent methods for quantifying daily MeP of individual cows [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of methods developed for quantifying GHG emissions from dairy cattle under research conditions. For example, enteric CH 4 emissions from dairy cattle can be measured by respiration chamber, sulphur hexafluoride tracer technique, ventilated hood /face mask and using the Greenfeed system (Hammond et al ., 2016; Zhao et al ., 2020). However, all these methods require substantial facilities and expertise to accurately quantify CH 4 emissions.…”
Section: Challenges For Quantifying Greenhouse Gas Emissions Through mentioning
confidence: 99%
“…In many cases, milk in developing countries comes from these smallholder systems. For instance, 85% of total Kenya milk production comes from smallholders (Gerosa and Skoet, 2013) and in Pakistan 95% of milk consumed is from local and unpackaged milk sources produced by smallholder farmers (Zia et al, 2011). Intensification of the dairy system is common in developing countries as a response to increased demand for milk.…”
mentioning
confidence: 99%
“…So too is the use of "sexed semen" during artificial insemination to lessen the likelihood of unwanted male calves from dairy cows, reducing the "waste" and overall emissions intensities of the products produced by the herd (Gerber et al 2013). Low methane herd management also works by manipulating the spaces in which cattle live: planting grasses that are easily digestible and shifting from unrestricted grazing systems to rotating systems means pastures recover quicker, suppressing the growth of less digestible weeds that slow growth and increase overall emissions (Zhao et al 2020).…”
Section: Herd Scale Technologiesmentioning
confidence: 99%